Reynolds privilege defence in Malaysia: a review of Dr Syed Azman Syed Ahmad Nawawi & Ors v. Dato’ Seri Hj Ahmad Said [2015] 7 CLJ 180 And Syarikat Bekalan Air Selangor Sdn Bhd v. Tony Pua Kiam Wee [2015] 8 CLJ 477:Part 1 - Sardar Baig, Farheen Baig; Ali Mohamed, Ashgar Ali (Malaysian Current Law Journal Sdn. Bhd., 2018)
The Reynolds privilege defence propounded in the well-known case of Reynolds v. Times Newspapers, 1 protects ‘responsible journalism’ in a claim for defamation. In deciding whether the publication occurred responsibly, Lord Nicholls set out ten indicative factors relating to the nature of the publication, such as the seriousness of the allegation, the nature of the information, its source, if steps taken to verify the information, the urgency of the matter, if comments were sought from the claimant or contained the gist of the claimant’s side of the story and the tone of the article, among others. The defendant would need to show that the publication was made responsibly or reasonably to establish a form of duty-interest qualified privilege. Since 2001, when Malaysia first saw the application of the Reynolds principle in Dato’ Seri Anwar Ibrahim v. Dato’ Seri Dr Mahathir Mohamad, 2 the Reynolds privilege defence has been used as a defence in many cases, and of such cases, Dr Syed Azman Syed Ahmad Nawawi & Ors v. Dato’ Seri Hj Ahmad Said3 and Syarikat Bekalan Air Selangor Sdn Bhd v. Tony Pua Kiam Wee, 4 at the Federal Court level which have endorsed the use of this defence and in doing so, both cases have established the guidelines for its application. Before the Reynolds privilege defence was established, it had been difficult to determine if a duty-interest privilege would apply to widespread publications, but this appears to be possible after the decision in Reynolds. On the other hand, the traditional common law qualified privilege is to be discussed in comparison, as the Reynolds privilege in England found its roots from this defence. It is the source for the development of the Reynolds privilege defence. The link between the two defences is so close that it is often pleaded together and treated as one and the same defence which is seen to inhibit the growth and proper use of the Reynolds privilege defence as a defence on its own.